THE ROLE OF COMMUNICATIVE COMPETENCE IN TEACHING ENGLISH LANGUAGE - Shaxnozabanu Joldasbaeva (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Usually teacher and students who are learning English communicate each other in their native language during the lesson. In consequence, many learners have difficulties in their speech. Because they may have following problems when they try to speak in English: afraid of breaking grammar rules, being excited or shying from audience, fear for making mistakes, lack of vocabulary, confusing what words should be used. So that every teacher must use communicative competence in teaching process. This is effective way to increase students’ speaking skill.